Measuring Economic Resilience of Tourism Villages: A Spatiotemporal Analysis of Pre and Post-Covid-19 Pandemic - Ariyani, Nafiah; Fauzi, Akhmad; Suherlan, Ade (Muhammadiyah University Press, 2023)
Tourist village plays an important role in rural development in Indonesia. Nevertheless, tourist village is also prone to external shocks such as national and global economic volatilities and recent public health events of the Covid-19 pandemic. This study attempts to analyze a temporal variations of tourist village economic resilience from pandemic shock in 24 tourist village destinations covering the period of 2019-2022 in Indonesia. A synthetic composite index of the Adjusted Mazziotta-Pareto Index (AMPI) was used to measure resilience, followed by clustering analysis to determine the typology of the resilience. The resilience index was composed of capacity and performance dimension related to resilience. The results show that most villages were severely affected in the first year of Covid-19, yet they recovered afterward, as indicated by positive differences in the AMPI index before and after Covid-19. This result shows that tourist villages in Indonesia have a tendency of strong capacity and performance to recover from the pandemic shock. The economic components of the capacity and performance were able to readjust after the pandemic indicating that these components are relatively adaptable to the shocks. The indicator that has the most significant influence on the typology of resilience in the performance dimension is the number of visitors. Meanwhile, the Development Village Index (DVI) indicator is the most significant influence on the capacity dimension.